Overview [in Achieving food security in southern Africa] - Haddad, Lawrence James (International Food Policy Research Institute, 1997)
The countries of Southern Africa are entering a new era. 1 Democratization, peace, and economic liberalization are important precursors of the kind of economic growth that can reduce poverty and raise incomes in a broad-based manner. Whether such a pattern of broad-based economic growth will occur will depend, in large part, on policy choices made in the countries of the region, at both the national and regional levels. More than at any time in the last 30 years, it will be lack of information and analysis rather than ideology and conflict that will constrain the ability of policymakers to make choices that bring about poverty reduction and food security, both now and in the future.